Effectiveness of long-term cluster training and traditional resistance training in enhancing maximum strength in young adults: a systematic review and meta-analysis - Cui, J.; Yu, Y.; Xu, Y.; Wu, H. (Frontiers in Physiology, 2025)
Background: It is still unclear whether traditional resistance training (TRT) provides the best or optimal stimulation for increasing maximum strength compared to cluster training (CT).